Knowing When to Ask: The Cost of Leaning In - Exley, Christine L.; Niederle, Muriel; Vesterlund, Lise (Journal of Political Economy, 2020)
Women’s reluctance to negotiate is often used to explain the gender wage gap, popularizing the push for women to “lean in” and negotiate more. Examining an environment in which women achieve positive profits when they choose to negotiate, we find that increased negotiations are not helpful. Women know when to ask: they enter negotiations resulting in positive profits and avoid negotiations resulting in negative profits. While the findings are similar for men, we find no evidence that men are more adept than women at knowing when to ask. Thus, our results caution against a greater push for women to negotiate.